Community assembly of glass frogs (Centrolenidae) in a Neotropical wet forest: a test of the river zonation hypothesis. (12th March 2018) - Rivera, Nelson; Folt, Brian
Abstract: The river zonation hypothesis predicts that abiotic and biotic conditions along riparian gradients drive variation in animal communities. Glass frogs are a diverse group of Neotropical anurans that use riparian habitats exclusively for oviposition and larval development, but little is known about how glass frog communities are distributed across riparian gradients. Here, we measured glass frog community assembly across a gradient of riparian habitats from first- to fifth-order streams at La Selva Biological Station, Costa Rica. We performed repeated nocturnal frog calling surveys and built occupancy and N- mixture abundance models to test for varying patterns of species occupancy, community assembly, species richness (α-diversity) and species turnover (ß-diversity). We observed significant differences in patterns of species occupancy and community assembly across a stream-order gradient: occupancy of two species increased with stream order ( Teratohyla pulverata, Hyalinobatrachium fleischmanni ), one species decreased ( Teratohyla spinosa ), and one species did not vary ( Espadarana prosoblepon ). We evaluated four a priori hypotheses describing how α- and ß-diversity of centrolenids are shaped across the riparian gradient; our data were most consistent with a pattern of nested assemblages and increasing species richness along the riparian gradient. Species-specific patterns of occupancy and abundance resulted in assemblage-level differences consistent with theoretical predictions for highly aquatic organisms along riparian gradients.